Effect of Moisture Content on Physical Properties of Black Pepper - Meghwal, Murlidhar; Goswami, T K (Journal of Agricultural Engineering, 2011)
Effect of moisture content on major physical properties of black pepper (Piper nigrum) was studied in moisture content range of 5 to 25% (db). It was observed that the physical properties viz., average length, width, thickness and equivalent diameter increased with increase in moisture content. The surface area, seed volume, thousand seed mass and true density increased from 66.67 to 72.52 mm², 46.38 to 52.43 mm³, 47.34 to 54.44 g and 1108 to 1509 kg.m?³, respectively, with increase in moisture content. However, in case of sphericity and specific surface area of black pepper, reverse trend was obtained. Similarly, angle of repose, terminal velocity and porosity increased from 30.86 degree to 38.23 degree , 8.8 to 10.5 m.s?¹ and 52 to 67%, respectively, with increase in moisture content. The bulk density increased initially from 534.6 to 562.8 kg.m?³, and then decreased from 562 to 504.6 kg.m?³ with increase in moisture content.